St. Augustine by Serge Lancel - Kevin Roy (Acta Theologica)
From text: The author, Serge Lancel of the University of Grenoble, is an acknowledged master of the ancient history of north Africa and has written major books on Carthage and Hannibal. This present biography of Augustine, translated from the French, is addressed to the common educated reader and is furnished with numerous erudite notes to inform the inquisitive where the evidence for his statements can be found. Lancel has been able to exploit the considerable number of new Augustinian documents discovered during the past 25 years, the new letters found by the Austrian scholar Johannes Divjak in two French libraries and the twenty-six new sermons found by Fançois Dolbeau in Mainz city library.